2006
DOI: 10.1038/sj.jcbfm.9600302
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Oxygen Metabolism in a Rat Model of Permanent Ischemia Using Positron Emission Tomography with Injectable 15O-O2

Abstract: The threshold of cerebral blood flow (CBF) into infarction in rats has been indicated to be similar to that in patients. However, CBF does not reflect metabolic function, and so estimations of oxygen metabolism have been required. Here, we estimated changes in oxygen metabolism after occluding the right middle cerebral artery (MCA) in rats using an injectable 15 O-O 2 we developed. A decrease in CBF (left: 0.6760.22 mL/min/g, right: 0.4460.17 mL/min/g, P < 0.05) and compensatory increase in the oxygen extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
6
17
0
Order By: Relevance
“…Although the steady-state method may induce systemic underestimation of CBF because of tissue heterogeneity between gray and white matter as compared with the bolus injection method in the human study (Kanno et al, 1984); however, the structure of the brain cortex in rats is not so complicated (Zilles and Wree, 1995), and the effect of brain tissue heterogeneity is not considered so significant as compared with the human brain because we placed ROIs on the cortices ( Figure 3A) and basal ganglia. The cerebral hemodynamic parameters of the normal rats using the present steady-state method were similar to the results reported previously using the bolus method (Magata et al, 2003;Temma et al, 2006;Tiwari et al, 2010), in which slightly higher values of OEF and CMRO 2 in normal rats were observed compared with those of normal human subjects. Differences in species and effects of anesthesia during the experiments are considered to provide these differences.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the steady-state method may induce systemic underestimation of CBF because of tissue heterogeneity between gray and white matter as compared with the bolus injection method in the human study (Kanno et al, 1984); however, the structure of the brain cortex in rats is not so complicated (Zilles and Wree, 1995), and the effect of brain tissue heterogeneity is not considered so significant as compared with the human brain because we placed ROIs on the cortices ( Figure 3A) and basal ganglia. The cerebral hemodynamic parameters of the normal rats using the present steady-state method were similar to the results reported previously using the bolus method (Magata et al, 2003;Temma et al, 2006;Tiwari et al, 2010), in which slightly higher values of OEF and CMRO 2 in normal rats were observed compared with those of normal human subjects. Differences in species and effects of anesthesia during the experiments are considered to provide these differences.…”
Section: Discussionsupporting
confidence: 88%
“…Although the P CO2 values in the MCAO model rats were significantly decreased compared with those in the normal rats, probably due to hyperventilation in a few rats during PET experiments, the CBF was not affected significantly because other blood gas data were not changed compared with those of normal rats. This effect of MCAO operation on the arterial blood gas data was similar to a previous report (Temma et al, 2006). The P CO2 values seem slightly higher and the P O2 values seem slightly lower in normal rats compared with those in humans probably due to the tendency of hypoventilation under anesthesia during Figure 1 Time-activity curves of the whole blood, plasma, and the whole brain using 15 O 2 -HbV with the steady-state method.…”
Section: Discussionsupporting
confidence: 87%
“…The third is the limited volume of the tracer solution that can be injected into small animals. To overcome these technical difficulties, some previous studies have applied 15 O gas inhalation through a tracheal tube (3), venous injection of 15 O-O 2 hemoglobin-containing red blood cells (4,5), 15 O-CO or O 2 hemoglobin-containing vesicles (6), or liposome-encapsulated hemoglobin (7). For quantitative measurements, the radioactivity of the cardiac chambers has been measured (3).…”
mentioning
confidence: 99%
“…Consequently, we found that hypertension intensifies metabolic disturbances after the onset of strokes. [90][91][92][93] Thus injectable 15 O-O 2 could be used reliably to estimate oxygen metabolism in an infarction rat model with PET. Furthermore, we developed molecular probes for nuclear medicinal imaging targeting β-secretase in the brain, acetylcholine esterase, cyclooxygenase-2 (COX-2), epidermal growth factor receptor (EGFR), and hepatic organic anion transporter (OATP1B1).…”
Section: Tc or 186/188mentioning
confidence: 99%